Impact of Late Quaternary climatic fluctuations on coastal systems: Evidence from high-resolution geophysical, sedimentological and geochronological data from the Java Island. (February 2022) - Novico, Franto; Menier, David; Mathew, Manoj; Ramkumar, Mu; Santosh, M.; Endyana, Cipta; Dewi, Kresna Tri; Kurniawan, Indra; Lambert, Clément; Goubert, Evelyne; Hendarmawan,
Abstract: The major climatic oscillations during the Quaternary Period significantly influenced the evolution and distribution of ancient and modern coastal systems. Here we investigate the morphology and sedimentary infilling of submerged Late Quaternary incised valleys along the northern coast of Java Island (Indonesia) using high-resolution geophysical, sedimentological and geochronological data. Our results indicate that the spatial development and morphology of the incised valleys are predominantly controlled by Quaternary glacial–interglacial eustatic fluctuations, within a marked subsiding setting. The valleys were incised during prominent Quaternary lowstands and most of the valley fill was emplaced during the last postglacial sea level rise. The valley fill forms a transgressive succession, consisting mainly of fluvial deposits at the base (possibly amalgamated from older sequences) overlain by shallow marine sediments and capped by hemipelagic deposits. The valley-fill architecture is strongly dependent on the valley morphology (depth of incision, width of the valleys, and extent of the intertidal zone). The shallow marine deposits contained within the narrow and linear valleys are mostly aggrading muds. The vertical incision and valley formation was chiefly controlled by the extent of glacial sea-level fluctuations. The studied sections represent the continental-offshore extension of a paleodeltaic system. The implication of our work is that even in predominantly enclosed shallow marine systems that are located distal to the shelf break, the response of the sedimentary system and ensuing stratigraphic configuration can be effectively impacted by the rapid and abrupt Quaternary global climatic transition and eustatic sea-level fluctuations. Highlights: Java Quaternary incised valley-fill consists of fluvial deposits at the base overlain by estuarine sediments and capped by hemipelagic deposits. The studied sections represent continental-offshore extension of the paleodeltaic system. Late Quaternary climatic and eustatic changes impacted sedimentary framework of enclosed shallow marine systems located distal to shelf break.